The Effect of Brand Name on Customer Loyalty in the Mobile Communication Industry in Ghana - Asiamah Yeboah, Dr.; Owusu-Mensah, Samuel; Kwaku Nimsaah, Wilson; Nicholas Oppong Mensah, Dr. (British Journal of Marketing Studies, 2013)
The mobile communication industry in Ghana cannot be successful without loyal customers. Thus, brand name is very critical factor to help retain customers thereby improving the bottom line of the firm. The purpose of this study was to investigate the extent to which brand name contributes to customer loyalty in mobile telecommunication brands in Ghana. The paper also finds out the factors that influence consumer choice of brand (mobile network) and why subscribers switch from one network to another. The study captured both qualitative and quantitative data. Data collection was conducted through a survey questionnaire comprising open and closed ended questions. To get the sample size for the study, 120 respondents were selected using simple random sampling but 150 were contacted because of data collection limitation such as non response. Statistical package for Social Sciences (SPSS) was used for data analysis. Statistical analysis includes Pearson correlation, logistic regression and descriptive statistics. Pearson correlation and regression were used to analyze the customer reasons for choosing a particular network as well as the relationship between customer association and brand attributes. The study found that, brand name does not really contribute to customer loyalty. Other factors such as the quality, price, availability, and sales promotion also contribute to customer loyalty. The study however revealed that, there are factors such as price, quality, price and quality and brand name that consumers consider when making a purchased decision, however, they mostly associate quality with the name of the mobile network brand purchase. Thus, any mobile network brand purchase is because of the quality but not necessarily the name